Implementasi Program Orientasi Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) di Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi - Eva Widia; Fitri Chairunnisa; Dessy Elliyana (EBISMAN eBisnis Manajemen, 2026)
This study aims to analyze the implementation of the Government Employees with Work Agreements (PPPK) orientation program at the Jambi Province Human Resources Development Agency (BPSDM). The research focuses on George C. Edward III’s 1980 policy implementation theory, which encompasses communication, resources, disposition, and bureaucratic structure. The research method used is descriptive qualitative. Data collection techniques were conducted through observation, interviews, and documentation, with informants determined using a purposive sampling technique. The results of the study indicate that the implementation of the PPPK Orientation Program has run quite well and has been able to improve participants’ understanding of the duties, functions, and core values ​​of the State Civil Apparatus (ASN). However, several obstacles remain in its implementation, namely internet and electricity network constraints, the lack of effective online learning, lack of participant discipline during the activity, and limited supervision and number of committee members. These obstacles affect the optimization of the learning process and the effectiveness of the online orientation activities. Therefore, efforts are needed to improve the quality of program implementation through the development of more interactive learning methods, the provision of adequate facilities, and further evaluation and mentoring to improve the competence and professionalism of ASN.